Management of Acute Traumatic Irreducible Metatarsophalangeal Joint Dislocation of the Lesser Toes: A Case Report - Ganesh Ramesh Shetty; Yogadeepan Dhakshinamurthi; Muthusaravanakumar Meignanaguru (Journal of Orthopedics and Joint Surgery)
Introduction: Irreducible metatarsophalangeal joint dislocations of lesser toes are not very common. Case description: We report a rare case of a 27-year-old male patient who was injured following a motorbike accident and dislocated his second, third, and fifth metatarsophalangeal joint (MTP) along with a fourth metatarsal neck fracture and same-side femur shaft fracture. The fifth MTP reduction was achieved by the closed method; however, the second and third MTP was not reducible despite multiple attempts at closed reduction. This called for open reduction and stabilization with K-wires. Clinical significance: This case report depicts the mechanism of injury, clinical signs, and structures preventing close and open reduction techniques through the dorsal approach is reviewed.